The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1159/000373938
|View full text |Cite
|
Sign up to set email alerts
|

Mitomycin C Induces Apoptosis in Rheumatoid Arthritis Fibroblast-Like Synoviocytes via a Mitochondrial-Mediated Pathway

Abstract: Background/Aims: Rheumatoid arthritis (RA) is a systemic chronic inflammatory disease characterised by prominent synoviocyte hyperplasia and a potential imbalance between the growth and death of fibroblast-like synoviocytes (FLS). Mitomycin C (MMC) has previously been demonstrated to inhibit fibroblast proliferation and to induce fibroblast apoptosis. However, the effects of MMC on the proliferation and apoptosis of human RA FLS and the potential mechanisms underlying its effects remain unknown. Methods: Cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 44 publications
2
34
0
Order By: Relevance
“…With further efforts, Ogando and his collogues identified miR-223 as a negative regulator of AHR/ARNT pathway by targeting ARNT, which negatively modulates the downstream Notch effectors [32]. Yan C et al identified mitomycin C induces apoptosis in rheumatoid arthritis fibroblast- Cellular Physiology and Biochemistry Cellular Physiology and Biochemistry like synoviocytes [33]. In our study, the expression level of miR-338-5p in RA synovium was significantly higher than that in normal synovium.…”
Section: Discussionsupporting
confidence: 45%
“…With further efforts, Ogando and his collogues identified miR-223 as a negative regulator of AHR/ARNT pathway by targeting ARNT, which negatively modulates the downstream Notch effectors [32]. Yan C et al identified mitomycin C induces apoptosis in rheumatoid arthritis fibroblast- Cellular Physiology and Biochemistry Cellular Physiology and Biochemistry like synoviocytes [33]. In our study, the expression level of miR-338-5p in RA synovium was significantly higher than that in normal synovium.…”
Section: Discussionsupporting
confidence: 45%
“…Thus, in vitro models that use human cells were developed to study the mechanism of RA and possible therapeutic approaches [20]. Therefore, primary human fibroblast-like synoviocytes from RA patients have been used to screen and study the unique effects of many drugs and phytochemicals [2123]. Despite the advantages of primary human fibroblast-like synoviocytes, they present certain inconveniences; for instance, primary mammalian cells have a limited replicable lifespan and ultimately enter a state of senescence in which they remain metabolically active but fail to proliferate.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, primary human fibroblast-like synoviocytes isolated from RA patients have been used to study the effects of a variety of drugs and phytochemicals [2123]. However, there are some difficulties in using RA-derived synovial fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…RA FLS can exhibit resistance to apoptosis caused by apoptotic stimuli, further facilitating FLS hyperplastic growth and the destruction of articular cartilage [22]. Therefore, inhibiting the proliferation of RA FLS and prpmoting apoptosis of FLS are therapeutic approaches for the treatment of RA.…”
Section: Discussionmentioning
confidence: 99%